The impact of climate change on farm production - Kołoszycz, Ewa (Wpływ zmian klimatu na produkcję w gospodarstwach rolnych, 2020)
Agricultural production is very sensitive to climate change, due to its natural nature. Farm owners wanting to limit the influence of this impact or to mitigate the effects, have introduced various adaptation measures. The aim of the article is to present the main effects of climate change on plant and animal production on farms and to show the possibilities and barriers to implementing adaptation measures. The article is a review study. The main effects of climate change impact include a reduction in the quantity and quality of production, weakening animal and plant resistance to diseases and pests, and reproduction problems. Adaptation measures are undertaken by farmers, but they can also be initiated by the farm’s external environment. The main challenges that farmers are facing include their adaptability problems and the way they perceive climate change and the risks associated with them
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 6, s. 115-126